Islamic leadership and employee satisfaction for developing world Islamic tourism: exploring a conceptual framework - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Hassan, Faridah (2017)
Human got Islamic values longer than 1400 years back when Holy Quran and Hadith were sent to the Messenger Prophet Mohammad(S) from Almighty Allah for the well-being of human being. According to the 103 rd Sura Al Asr in Quran, “human being is in loss except those who have Iman, Patience and Constancy.” Leadership behavior is developing over time, but leaders apply different theories in managing people that they think best though most employees are not satisfied. In most cases, first, leaders are driven by company objectives, then they drive employees, but employees are the most valuable part to achieve organizational objectives in world Islamic tourism industry. So, leadership theory should be developed a lot more as before since it has opportunity to develop employees in organizations until employees are satisfied. Clearly there are still problems in leadership development in organizations because leaders are treating employees according to their conventional values. Dissatisfaction is happening when leaders fail to lead the organizational people in appropriate way. Whatever is the leadership situation in an organization can be solved by applying Islamic principles which have supreme value in controlling human behavior at work. It is thought that Islamic value is highest ethical values that has been proved all the times and can be achieved by every leader if they want to satisfy employees since human-made ethical values has failed to do that in almost all cases all the times. Main objective of the study is to develop a conceptual framework with a set of relationships between appreciation and Islamic values and employee satisfaction with leaders. Islamic values for rational benefit and rational appreciation would be effective for organizations for changing leaders’ and followers’ ways they think and practice. Appreciation causes effective transformation leadership, commitment and satisfaction with management, where transformation leadership and commitment are playing roles as mediating variables. Islamic values and appreciation are exogenous variables and satisfaction with leaders is endogenous variable.